Comparison of Planning Quality and Efficiency Between Conventional and Knowledge-based Algorithms in Nasopharyngeal Cancer Patients Using Intensity Modulated Radiation Therapy - Chang, Amy T Y; Hung, Albert W M; Cheung, Fion W K; Lee, Michael C H; Chan, Oscar S H; Philips, Helen; Cheng, Yung-Tang; Ng, Wai-Tong (International journal of radiation oncology, biology, physics, 2016)
Intensity modulated radiation therapy (IMRT) is widely used to achieve a highly conformal dose and improve treatment outcome. However, plan quality and planning time are institute and planner dependent, and no standardized tool exists to recognize an optimal plan. RapidPlan, a knowledge-based algorithm, can generate constraints to assist optimization and produce high-quality IMRT plans. This report evaluated the quality and efficiency of using RapidPlan in nasopharyngeal carcinoma (NPC) IMRT planning. RapidPlan was configured using 79 radical IMRT plans for NPC; 20 consecutive NPC patients indicated for radical radiation therapy between October 2014 and May 2015 were then recruited to assess its performance. The ability of RapidPlan to produce acceptable plans was evaluated. For plans that could not achieve clinical acceptance, manual touch-up was performed. The IMRT plans produced without RapidPlan (manual plans) and with RapidPlan (RP-2 plans, including those with manual touch-up) were compared in terms of dosimetric quality and planning efficiency. RapidPlan by itself could produce clinically acceptable plans for 9 of the 20 patients; manual touch-up increased the number of acceptable plans (RP-2 plans) to 19. The target dose coverage and conformity were very similar. No difference was found in the maximum dose to the brainstem and optic chiasm. RP-2 plans delivered a higher maximum dose to the spinal cord (46.4 Gy vs 43.9 Gy, P=.002) but a lower dose to the parotid (mean dose to right parotid, 37.3 Gy vs 45.4 Gy; left, 34.4 Gy vs 43.1 Gy; P<.001) and the right cochlea (mean dose, 48.6 Gy vs 52.6 Gy; P=.02). The total planning time for RP-2 plans was significantly less than that for manual plans (64 minutes vs 295 minutes, P<.001). This study shows that RapidPlan can significantly improve planning efficiency and produce quality IMRT plans for NPC patients.